2016
DOI: 10.1002/pro.3043
|View full text |Cite
|
Sign up to set email alerts
|

Activation of bacterial lytic polysaccharide monooxygenases with cellobiose dehydrogenase

Abstract: Lytic polysaccharide monooxygenases (LPMOs) represent a recent addition to the carbohydrate-active enzymes and are classified as auxiliary activity (AA) families 9, 10, 11, and 13. LPMOs are crucial for effective degradation of recalcitrant polysaccharides like cellulose or chitin. These enzymes are copper-dependent and utilize a redox mechanism to cleave glycosidic bonds that is dependent on molecular oxygen and an external electron donor. The electrons can be provided by various sources, such as chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 54 publications
6
97
2
Order By: Relevance
“…Prereduction of CDH with cellobiose was performed under atmospheric conditions with or without catalase to investigate the effect of the by‐product H 2 O 2 on the observed rate. The presence of H 2 O 2 had no effect on the LPMO reduction rate and in both cases, the apparent bimolecular rate constant for the CDH oxy+ /LPMO interaction was 1.27 × 10 6 m −1 ·s −1 , which is similar to the reported value for Ch CDH/LPMO (0.63 × 10 6 m −1 ·s −1 ; ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Prereduction of CDH with cellobiose was performed under atmospheric conditions with or without catalase to investigate the effect of the by‐product H 2 O 2 on the observed rate. The presence of H 2 O 2 had no effect on the LPMO reduction rate and in both cases, the apparent bimolecular rate constant for the CDH oxy+ /LPMO interaction was 1.27 × 10 6 m −1 ·s −1 , which is similar to the reported value for Ch CDH/LPMO (0.63 × 10 6 m −1 ·s −1 ; ).…”
Section: Resultssupporting
confidence: 84%
“…While Ch CDH and CDH oxy+ transfer electrons to the LPMO with similar efficiencies, they produce different amounts of H 2 O 2 , which translates into different LPMO activities. In accordance with the correlation between H 2 O 2 production by the CDH and LPMO activity, it has been noted earlier that the rate of Ch CDH‐driven LPMO activity is similar to the rate of H 2 O 2 production by Ch CDH in reactions with O 2 as the only electron acceptor . It has been suggested that H 2 O 2 ‐driven LPMO activity implies that, when once reduced, an LPMO could carry out multiple oxidative cleavages .…”
Section: Resultssupporting
confidence: 79%
“…In this respect, it is interesting to note the relatively stable kinetics obtained with CDH (Fig. A), which is known to form H 2 O 2 in a controlled manner at rates comparable to observed catalytic rates of LPMOs . In line with the recent claims by Bissaro et al, it is tempting to speculate that in these reactions the produced H 2 O 2 is consumed immediately by the LPMO, avoiding H 2 O 2 accumulation and thus oxidative inactivation.…”
Section: Discussionsupporting
confidence: 74%
“…Reactions with various electron‐donating systems (ascorbic acid, CDH, or natural compounds in steam‐exploded birch) did not reveal differences in terms of the LPMO's ability to recruit electrons from varying sources. While progress curves with CDH showed that product formation increased during most of the monitored incubation period, the reactions with ascorbic acid, expectedly, terminated before the monitoring period was over (Fig. ).…”
Section: Discussionmentioning
confidence: 98%
“…93,110,119,130 More recently, Loose et al demonstrated activation of a bacterial AA10 LPMO by a CDH from the fungus Myriococcum thermophilum . 158 The interactions of CDH with LPMOs are discussed further in sections 4 and 5.…”
Section: Industrial Use Of Lpmosmentioning
confidence: 99%